2021
DOI: 10.1002/aws2.1215
|View full text |Cite|
|
Sign up to set email alerts
|

Microwave cell lysis for ADDA‐ELISA analysis of total microcystins and nodularins

Abstract: A fast and effective microwave treatment procedure was developed for the ADDA-enzyme-linked immunosorbent assay analysis of total extracellular and intracellular microcystins and nodularins in drinking water and ambient water. This microwave treatment procedure for a full batch of samples required 10-20 min versus the 3-4 hr typically needed for three freeze/thaw cycles. The obtained lowest-concentration minimum reporting level and method detection limit were 0.21 and 0.09 μg/L microcystin-LR (MC-LR) equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Microwave for 3 to 5 min achieved adequate MC-LR recovery in most samples. This was relatively consistent with other studies that demonstrated 9 to 20 min of microwave enabled recovery of total MCs [ 15 , 18 ]. However, recovery of MC-LR by microwave for cells suspended in CRW was lower than that applied to cells in phosphate buffer, and recovery of MC-LR in the control CRW showed greater variation when compared with the other lysis methods.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Microwave for 3 to 5 min achieved adequate MC-LR recovery in most samples. This was relatively consistent with other studies that demonstrated 9 to 20 min of microwave enabled recovery of total MCs [ 15 , 18 ]. However, recovery of MC-LR by microwave for cells suspended in CRW was lower than that applied to cells in phosphate buffer, and recovery of MC-LR in the control CRW showed greater variation when compared with the other lysis methods.…”
Section: Discussionsupporting
confidence: 92%
“…Such variation from microwave should be addressed by using sealed containers (able to withstand pressure) to hold samples during microwave, though this practice can limit sample volume relative to other methods [ 18 ]. Additionally, microwave without allowing samples to boil can minimize sample loss (and potential associated error) [ 15 ]. Microwave for 10 to 20 min has been shown to be more effective for MC recovery than three freeze-thaw cycles in natural bloom samples, and microwave lysis does not degrade multiple MC congeners [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations